Barney's Favorite Mother Goose Rhymes - White, Stephen; Illustrated by Eubank, Mary Grace (Texas Barney, 1993)
Traditional and new rhymes featuring Barney.
Include Color Illustrations
Keywords: Nursery rhymes -- Children's poetry